Morphological differentiation between seven brazilian populations of Haemagogus Capricornii and HG. Janthinomys (Diptera: Culicidae) using geometric morphometry of the wings - Olsson Freitas Silva, Shayenne (2024)
Introduction: Haemagogus capricornii and Hg. janthinomys females are considered morphologically indistinguishable. We analyzed morphometric variability between Brazilian populations of these species using wing geometric morphometry. Methods: Size and shape at intra- and interspecific levels were analyzed in 108 Hg. capricornii and Hg. janthinomys females. Results: Geometric morphometry indicated size and shape variables can differentiate these species at interspecific level. However, at intraspecific level, results show relative differentiation. Two populations of Hg. capricornii had a smaller centroid size with no significant differences between them, whereas all Hg. janthinomys populations showed significant differences. Conclusions: Both species were correctly identified by geometric morphometry.